Do Bubbles occur in the Gold Price? An investigation of Gold Lease Rates and Markov Switching Models - LUCEY, BRIAN (My University, 2014)
We assess whether two classes of bubbles occur in the spot price of gold, rational speculative and periodically bursting bubbles, using gold?s lease rates for the first time in the literature as a measure of its fundamental value. This question is of particular significance as these are the only observable market measures of a yield that can be earned from gold. We use unit root and cointegration tests to look for rational speculative bubbles and Markov Switching Augmented Dickey-Fuller tests for periodically bursting bubbles. ADF and cointegration tests point to a rational speculative bubble. The more theoretically valid Markov Switching ADF test gives mixed evidence. No bubble is found to be present if we allow the variance to switch between regimes, the gold and its lease rate relationship is instead characterised by high and low variance periods. Imposing a constant variance gives evidence of a bubble for the 2, 3 and 12 month lease rates, but no bubble when we use the 1 and 6 month rates as determinants.
PUBLISHED
Keywords: Gold; Markov; International Integration